2010
DOI: 10.1503/cmaj.101311
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and stroke rehabilitation

Abstract: A cupuncture has been used in traditional Chinese medicine for more than 3000 years as a treatment for many diseases and is especially well accepted in China for rehabilitation after stroke.1 Several systematic reviews have suggested that acupuncture is effective in stroke rehabilitation; [2][3][4][5][6] however, the results were inconclusive because of extensive heterogeneity across trial outcomes and a high risk of bias.In this issue, Kong and colleagues report their finding of no specific effect of acupunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 11 publications
(12 reference statements)
0
24
0
3
Order By: Relevance
“…Also, Wu et al 7 concluded that there is no clear evidence relating to the effects of acupuncture in subacute or chronic stroke. The systematic review performed for this report study focused on uncovering evidence of the effects of acupuncture for shoulder pain after stroke, instead of a broader assessment of pain after stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Wu et al 7 concluded that there is no clear evidence relating to the effects of acupuncture in subacute or chronic stroke. The systematic review performed for this report study focused on uncovering evidence of the effects of acupuncture for shoulder pain after stroke, instead of a broader assessment of pain after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Recent articles reviewing the efficacy and safety of acupuncture in stroke have appeared, but no clear effects of acupuncture were shown. 7,9 In the literature, there has been no systematic review assessing the effects of acupuncture for shoulder pain following stroke. Therefore, the aim of this study was to summarize and evaluate the results of relevant trials involving this area.…”
mentioning
confidence: 99%
“…In a prospective randomized controlled trial, carried out in a stroke rehabilitation unit in Hong Kong among 106 patients with moderate or severe functional impairment 3 to 15 days after acute stroke, no additional improvement was shown in motor impairment or disability over a 10 week period in patients receiving traditional Chinese manual acupuncture as compared with the control . Moreover, systematic reviews and meta-analysis of nineteen trials involving 1576 patients did not find a statistically significant therapeutic benefit of traditional acupuncture on motor recovery for patients with subacute or chronic stroke Wu et al, 2008). However, a more recent comparative study of acupuncture versus EA regarding their effectiveness in treating post-stroke spastic paralysis showed that they were both effective and that EA was superior to traditional acupuncture alone (Yue et al, 2012).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Acupuncture also induces changes in regional cerebral blood flow surrounding infarcts [6]. However, to date, no convincing scientific evidence from clinical trials has been published showing acupuncture to be effective as a therapy after stroke in enhancing functional improvement [7][8][9][10]. Furthermore, the neural mechanism of acupuncture in stroke patients has not yet been well defined [2].…”
Section: Introductionmentioning
confidence: 99%